Postcards from Abroad - Blanca Callén; Melisa Duque; Elsa Callén; Pilar Andrés; Azucena González San Emeterio; Santiago Gallego; Samu Céspedes; Miquel Caballé; Cristina Lampón; Noelia Martínez; Oscar Martínez-Rivera (Diseña, 2023)
In this section called ‘postcards from abroad’ we propose to diversify and open up the understandings and practices of repair itself, engaging material repair in conversation with other types of repair, coming from fields of creation and knowledge other than design. Although there could be many other ‘postcards’ from different reparative places, here we invited: DNA repair in the field of genetics; soil bioremediation from the perspective of edaphology; psychotherapy as a form of emotional and psychological ‘repair’; memory repair from the field of restorative justice and human rights; home maintenance and cleaning as a form of domestic infrastructure repair and care; repair of electrical and electronic devices by activist collectives for waste prevention; repair of scientific observation instruments in the field of astronomy; and neuro-rehabilitation and physical rehabilitation from the first-person experience of long COVID. We hope these postcards provide a plurality of visions and actions on repair that might lead to resonances, inspirations, and cross-fertilizations among the various forms of repair.